2002
DOI: 10.5642/aliso.20022102.03
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Failure and Loss of Reproductive Capacity as a Factor in Extinction: A Nine-Year Study of Dedeckera Eurekensis (Polygonaceae)

Abstract: A BSTRACTMany long-lived perennial spe cies exhibit lowered reproductive capacity. Early studies of reproduct ive success in Dedeck era eurek en sis (Po lygonacea e) demonstr ated that the spe cie s e xhibited extremel y low reproducti ve su cce ss , low see dlo vule (S/O ) ratios (i.e., the percentage of ovules that produce filled seeds; 2.5 %), low germinability of filled seeds (3.5%), low seedling survivorship (11 .1% ), and lack of recruitment in natural populations. These results were attributed to geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(23 citation statements)
references
References 21 publications
3
20
0
Order By: Relevance
“…Moreover, we found higher S/O ratios in taxa that had some degree of selfing. These data are consistent with other studies showing higher S/O ratios in taxa that are selfed rather than outcrossed (Wiens 1984;Wiens et al 1987Wiens et al , 2002Meney et al 1997;.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…Moreover, we found higher S/O ratios in taxa that had some degree of selfing. These data are consistent with other studies showing higher S/O ratios in taxa that are selfed rather than outcrossed (Wiens 1984;Wiens et al 1987Wiens et al , 2002Meney et al 1997;.…”
Section: Discussionsupporting
confidence: 95%
“…However, environmental fluctuation, as measured by precipitation, did not appear to be a factor contributing to low seed/ovule ratios and high embryo abortion in this taxon. These data are consistent with other studies that have demonstrated constancy of S/O ratios over multiple years and correlation of resource availability with greater flower and seed production but not embryo abortion (Maun and Cavers 1971;Stephensen 1984;Wiens 1984Wiens , 1989Harper and Wallace 1987;Roitberg 1989, 1994;Herrera 1991;Wiens et al 2002).…”
Section: Discussionsupporting
confidence: 93%
“…Background extinctions are invariably the result of a series of interacting factors and their multiplicative effects (Gittleman & Gompper, 2001). Likewise, our studies of higher plants show that population decline is related to multiple environmental causes and genetic factors (Wiens et al ., 1989, 2002, 2011).…”
Section: Clarifying the Issue Of Extinction Causementioning
confidence: 66%
“…Unfortunately, with the exception of Harper (1977), their statements are brief and without elaboration: Jepsen, Mayr & Simpson (1949), Raup (1978, 1984, 1991), McKinney (1993), Rose (1998), Mayr (2001), and no doubt others. Mayr (2001) stated it clearly: ‘Whenever a population is no longer able to reproduce enough offspring to replace losses from natural causes, it will become extinct.’ Perhaps the lack of amplification by these authors was due to the paucity of fecundity data to support the hypothesis (Wiens et al ., 2002, 2011; Schoener et al ., 2003).…”
Section: The Loss Of Reproductive Fitness and Extinction: A Theorem Tmentioning
confidence: 91%
See 1 more Smart Citation